A Taxonomic Revision of Mezoneuron (Leguminosae: Caesalpinioideae: Caesalpinieae) - Clark, Ruth P. (Phytotaxa, 2016)
Mezoneuron is a genus of 24 species that has often formerly been understood to belong within Caesalpinia s.l., but which on the basis of recent molecular evidence, along with a number of other segregates, is now considered a distinct genus. Mezoneuron is broadly distributed, with its centre of diversity in South East Asia, but with species also in Africa, Australasia, and Hawaii. This is the first study to conduct a complete revision of the genus across its geographical range. A key to the species is provided, along with full species descriptions, distribution maps, preliminary conservation assessments, and selected illustrations. This study examines the morphological evidence supporting the generic status of the group, particularly of the fruit type, which has traditionally been considered its defining feature.